Optimization and Characterization of Adsorbent from Palm Kernel Shell Waste Using H3PO4 Activator - Herlambang, M. Julian; Ramandani, Adityas Agung; Cendekia, Devy; Alvita, Livia Rhea; Wulandari, Yeni Ria; Shintawati, Shintawati; Purnani, Mawar Siti; Efendi, Dimas Amirul Mukminin Nur (Universitas PGRI Madiun, 2023)
Palm kernel shell is solid waste produced from the processing of crude palm oil (CPO). In this context, phosphoric acid (H3PO4) serves as an essential activator for producing an adsorbent with maximum micropore under operating conditions at a temperature of <450oC. Therefore, this study aimed to determine the optimal adsorbent condition of the palm kernel shell using H3PO4activator. The production process was optimized using Response Surface Methodology (RSM) and Central Composite Design (CCD) methods with activator concentration variations of 4%, 5%, and 6%, at activation times of 23 hours, 24 hours, and 25 hours, respectively. The quality of the adsorbent produced fulfilled SNI standard 06-3730-1995, characterized by water content of 1.001%, ash content of 5.767%, missing substance level of 18.932%, and fixed carbon content of 75.301%. Furthermore, this work effectively optimized the RSM and CCD adsorbent production process, achieving 4.785% variation in activator concentration and 24.679 hours activation time.